2023
DOI: 10.1039/d2tb02630a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall superparamagnetic iron oxide nanoparticles for enhanced tumor penetration

Abstract: The intrinsic pathological characteristics of tumor micrenvironment restrict the deep penetration of nanomedicines by passive diffusion. Magnetophoresis is a promising strategy to improve the tumor penetration of nanomedicines aided by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been observed that the size and surface coating characteristics of the NPs ultimately determine their tissue deposition [ 181 , 182 , 183 ]. Additionally, smaller NPs (20 nm or less in diameter) have been found to penetrate tumor tissue more effectively [ 183 , 184 ]. It is worth noting that smaller particles have a tendency to remain in circulation for longer periods [ 185 , 186 ].…”
Section: Immunohistological Studies For Complex Biological Structuresmentioning
confidence: 99%
“…It has been observed that the size and surface coating characteristics of the NPs ultimately determine their tissue deposition [ 181 , 182 , 183 ]. Additionally, smaller NPs (20 nm or less in diameter) have been found to penetrate tumor tissue more effectively [ 183 , 184 ]. It is worth noting that smaller particles have a tendency to remain in circulation for longer periods [ 185 , 186 ].…”
Section: Immunohistological Studies For Complex Biological Structuresmentioning
confidence: 99%
“…an injection into the blood circulation, the particles will be in immediate contact with endothelial cells, which form the inner cell layer of blood vessels. While numerous studies have thoroughly examined the cellular uptake of magnetic nanoparticles by cancer cells, [21][22][23] our ndings provide valuable insights into the internalization of these nanoparticles by endothelial cells. Tumor endothelial cells differ from endothelial cells in normal tissues, including the presentation of certain surface molecules.…”
Section: Introductionmentioning
confidence: 99%